HUBUNGAN KEMANDIRIAN BELAJAR DENGAN CAPAIAN EVALUASI KOGNITIF PADA MATA PELAJARAN EKONOMI SMA NEGERI 3 - Syarif Nasarudin Aulia Zulfi; Aminuyati Aminuyati; Witarsa Witarsa (Universitas Tanjungpura, 2019)
AbstractThis study aims to determine the relationship between learning independence and the achievement of cognitive evaluation of students of class XII IPS in SMA 3 Pontianak. The research method used is correlational with quantitative research. The research sample used in the study was class XII IPS 3 by using Purposive Sampling or samples carried out based on specific goals. The data used is a questionnaire to find out the independence of learning and documentation to find out the achievements of cognitive evaluation through the results of the final evaluation of the odd semester of the 2018/2019 academic year. The results showed that there was a significant relationship between variables X and Y variables. This was evidenced by the results of the calculation of the t test of 2.132, while in t table 1.69092 at the significance level of 5% which means that Ha is accepted. Product moment correlation value is 0.343. While the linear regression coefficient is obtained at 0.600 and the coefficient of determination is 11.8%. Meanwhile, the remaining 88.2% is a factor that has a relationship with the Y variable from other factors not examined by the researcher. Keywords: Achievement of Cognitive Evaluation, Economic Subjects, Learning Independence